2013
DOI: 10.1149/2.012402jss
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg Doping on the Electrical Characteristics of High Performance IGZO Thin Film Transistors

Abstract: In this work, we report that the electrical characteristics of Indium-Gallium-Zinc-Oxide Thin Film Transistors (IGZO-TFTs) can be improved by Mg doping in the IGZO layer. Several composite IGZO/Mg-doped IGZO channel structures were employed. With appropriate Mg-doped IGZO thickness, the electrical properties such as mobility, subthreshold swing (S.S.) and on/off ratio can be significantly improved by Mg doping. Mg doping in IGZO layer can stabilize device performance whatever the device is stressed under posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…In our search, we therefore scan over a range of target band gap values; 0, 0.25, 0.5, 0.75, and 1 eV larger than that of IGZO. In DFT@PBEsol, the bandgap of a-IGZO is 2.2 eV, Which underestimates the experimental value of 3.0–3.6 33,119,120 as can be expected semi-local DFT. Since the bandgap is large enough to always be qualitatively correct.…”
Section: Methodscontrasting
confidence: 59%
See 1 more Smart Citation
“…In our search, we therefore scan over a range of target band gap values; 0, 0.25, 0.5, 0.75, and 1 eV larger than that of IGZO. In DFT@PBEsol, the bandgap of a-IGZO is 2.2 eV, Which underestimates the experimental value of 3.0–3.6 33,119,120 as can be expected semi-local DFT. Since the bandgap is large enough to always be qualitatively correct.…”
Section: Methodscontrasting
confidence: 59%
“…Until recently, numerous primary and binary oxides were reported to display mobilities reaching sometimes well over 200 cm 2 V −1 s −1 . 22–36…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the output characteristics of three devices with different channel length (L): 15, 20, 25 and 30 μm. As can be observed, there is significant increase in drain current when the gate voltage changes from 4 to 6 V. A similar behavior was found for IGZO-TFTs, which was attributed to the formation of oxide at the interfacial layer between Mg doped IGZO and Ti electrodes [21] .…”
Section: Analysis and Discussionsupporting
confidence: 74%
“…The extracted optical bandgaps are 3.34 eV, 3.38 eV and 3.40 eV for the a-IGZO films deposited at oxygen flow rates of 0, 2 and 3 sccm. Bandgaps of a-IGZO semiconductors have been reported to be 2.9-3.4 eV [13,57,59]. Yabuta et al [57] found that the optical bandgap of the a-IGZO semiconductor could increase from 3.06 eV to 3.11 eV when the oxygen content increased from 1% O 2 to 5% O 2 .…”
Section: Bmentioning
confidence: 99%
“…Amorphous IGZO can be deposited by a sputter at room temperature (RT). However, the gate insulators are conventionally grown by CVD [13,14] or atomic layer deposition [15] at high process temperatures. The spin-on dielectrics have been considered as potential candidates for replacing dielectric layers that deposited by CVD.…”
Section: Introductionmentioning
confidence: 99%